Early host immune responses in a human organoid-derived gallbladder monolayer to Salmonella Typhi strains from patients with acute and chronic infections: a comparative analysis - Salerno-Goncalves, Rosângela; Chen, Haiyan; Bafford, Andrea C.; Izquierdo, Mariana; Hormazábal, Juan Carlos; Lagos, Rosanna; Tettelin, Hervé; D’Mello, Adonis; Booth, Jayaum S.; Fasano, Alessio; Levine, Myron M.; Sztein, Marcelo B. (Frontiers in Immunology, 2024)
Salmonella enterica serovar Typhi (S. Typhi), a human-restricted pathogen, invades the host through the gut to cause typhoid fever. Recent calculations of the typhoid fever burden estimated that more than 10 million new typhoid fever cases occur in low and middle-income countries, resulting in 65,400-187,700 deaths yearly. Interestingly, if not antibiotic-treated, upon the resolution of acute disease, 1%-5% of patients become asymptomatic chronic carriers. Chronically infected hosts are not only critical reservoirs of infection that transmit the disease to naive individuals but are also predisposed to developing gallbladder carcinoma. Nevertheless, the molecular mechanisms involved in the early interactions between gallbladder epithelial cells and S. Typhi remain largely unknown. Based on our previous studies showing that closely related S. Typhi strains elicit distinct innate immune responses, we hypothesized that host molecular pathways activated by S. Typhi strains derived from acutely and chronically infected patients would differ. To test this hypothesis, we used a novel human organoid-derived polarized gallbladder monolayer model, and S. Typhi strains derived from acutely and chronically infected patients. We found that S. Typhi strains derived from acutely and chronically infected patients differentially regulate host mitogen-activated protein kinase (MAPK) and S6 transcription factors. These variations might be attributed to differential cytokine signaling, predominantly via TNF-α and IL-6 production and appear to be influenced by the duration the isolate was subjected to selective pressures in the gallbladder. These findings represent a significant leap in understanding the complexities behind chronic S. Typhi infections in the gallbladder and may uncover potential intervention targets.